PERAN TOKOH BALIAN DALAM NOVEL UPACARA KARYA KORRIE LAYUN RAMPAN PENDEKATAN: STRUKTURAL LEVI-STRAUSS - Yolanda Nesi Mau; Widowati Widowati (Universitas Sarjanawiyata Tamansiswa, 2016)
The purpose of this study is as follows. (1) describe novel structural Upacara in the view of Levi-Strauss. (2) Describe the conflict contained in the novel Upacara. (3) Describe the role of shaman that exist in the novel Upacara. This type of qualitative descriptive study. The data in this study is mitem-mitem that describes the structure of the novel, the conflict and the role of shaman figures. Source of data used is primary data source in the form of a novel Upacara by Korrie Layun Rampan. Instruments in this study are the researchers themselves who are already equipped with the concepts, theories of myth, ritual and structuralism Levi-Strauss and other supporting theory. Data collection methods used in this study is a formal method. The data collection technique used is the technique of reading and quotation. Data analysis method used in this study is a qualitative method. The data analysis technique used is a descriptive qualitative technique that exposes and describes the data that has been obtained is clear and rests on a structural view of Levi-Strauss. The results of this study are as follows. (1) The structure of the novel Upacara was divided into 18 episodes. Each episode that illustrates the relationships and opposition antarmitem showing the overall meaning of the conflicts in a society of Dayak Benuaq, and the role of balian in leading the ceremonies. (2) Conflicts are contained in the novel Upacara by Korrie Layun Rampan happened between communities of Dayak Benuaq and strangers. Community Dayak Benuaq trying to protect the natural and their trust. The foreigners trying to destroy the nature that has been preserved and introduce God or religion to tribal communities of Dayak Benuaq. (3) The role of leaders healers are contained in the novel Upacara is as traditional elders, as leader of traditional ceremonies, as interpreter recovered, and as a judge fairly.